STUDI DAYA SERAP WARNA SERAT TANDAN PISANG DENGAN PEMBANDING SERAT ABAKA DAN SERAT SABUT KELAPA - Christmastuti Nur (Arena Tekstil, 2018)
Exploration of banana peduncle waste is an attempt to search new product material alternatives. The purpose of this research is to reveal the character of banana peduncle fiber especially in its ability to absorb the color compared to abaca fiber and coir fiber. The color intensity test was conducted by calculating the luminance or the intensity of light which was reflected back by the surface area of the fiber. The result of this research was the bleached banana peduncle fiber generates more vivid and brighter color than the unbleached banana peduncle fiber. The unbleached one was similar to abaca fiber especially in absorbing red color (ratio = 1.00) and blue color (ratio = 1.01), however, it was lower than abaca fiber in absorbing green color (ratio = 0.98) and yellow color (ratio = 0.92). Thus, the unbleached banana peduncle fiber can be used effectively to perform color gradation of red and blue. Comparing to coir fiber, the absorption of banana peduncle fiber toward red, green, blue, and yellow color was higher. This research can be applied in coloring process of product material because it can accelerate production process and save production cost.